Effect of chemically grafted CNTs onto carbon fiber on the mechanical properties of fiber metal laminates. (January 2022) - Zhang, Yanan; Liu, Xinyang; Ji, Fan; Liu, Cheng; Hu, Yubing; Jiang, Wei; Xing, Yifan
Abstract: This study explores the influence of the chemical grafting of CNTs on the surface of carbon fibers (CFs) on the mechanical properties of Ti/CFRP laminates. After grafting CNTs onto oxidized CFs, Ti/CFRP laminates were prepared through vacuum-assisted resin-transfer molding (VARTM). Then, the bending performance, interlayer shear performance, static press-through, and impact resistance of the modified laminates were systematically studied. Compared with the original laminates, the bending strength and interlaminar shear strength were all remarkably improved. The static press-through tests showed a linear relationship between the energy absorption and laminate thickness, and the maximum failure load was slightly lower than that of the original specimen. The introduction of CNTs improved the deformation resistance of the laminate by increasing the critical fracture energy. Under a certain impact energy, the damaged area of the modified laminates decreased by a quarter without matrix or fiber delamination. Graphical abstract: Image 1 Highlights: a) The effect of chemical grafting of CNTs on the surface of carbon fiber on the mechanical properties of Ti/CFRP laminates was systematically studied. b) The bending strength and interlaminar shear strength of modified Ti/CFRP laminates were significantly improved. c) The impact damage area was reduced due to the pull-out and fracture of CNTs, which hindered the lateral transmission of cracks.